A Delicate Balance: Mobility and Access Needs, Expectations and Costs - Metz, David (International Transport Forum Discussion Papers, 2011)
Mobility has been central to economic development and social progress in the modern era. There is emerging evidence, however, that personal daily travel has recently ceased to grow in developed economies. The historic increase in mobility served to enlarge access to desired destinations and allowed more choice of jobs, homes, shops schools etc within acceptable travel times. Access and choice increase in proportion to the square of the speed, whereas choice of any given kind of destination is characterised by declining marginal utility. Accordingly, saturation of daily travel demand is to be expected and is a likely explanation for the observed cessation of per capita growth of personal travel